2021
DOI: 10.1002/esp.5043
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and evolution of supraglacial hummocks on debris‐covered Himalayan glaciers

Abstract: Thick supraglacial debris layers often have an undulating, hummocky topography that influences the lateral transport of debris and meltwater and provides basins for supraglacial ponds. The role of ablation and other processes associated with supraglacial debris in giving rise to this hummocky topography is poorly understood. Characterizing hummocky topography is a first step towards understanding the feedbacks driving the evolution of debris-covered glacier surfaces and their potential impacts on mass balance,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 63 publications
2
22
0
Order By: Relevance
“…Even so, some of the patterns observed here can help to inform interpretations of process-landform relationships. The length-scales used in the domain set-up (∼10 2 m) are generally consistent with those observed in topographic features of modern debris-covered valley glaciers (Bartlett et al, 2020), and for simulations that produced significant postglacial relief, moraine ridges are similarly spaced. This spacing is also consistent with some observed hummocky moraine tracts (albeit in only one dimension) (Johnson and Clayton, 2005), and is inherited from the prescribed spacing of debris source nonuniformity.…”
Section: Discussionsupporting
confidence: 61%
“…Even so, some of the patterns observed here can help to inform interpretations of process-landform relationships. The length-scales used in the domain set-up (∼10 2 m) are generally consistent with those observed in topographic features of modern debris-covered valley glaciers (Bartlett et al, 2020), and for simulations that produced significant postglacial relief, moraine ridges are similarly spaced. This spacing is also consistent with some observed hummocky moraine tracts (albeit in only one dimension) (Johnson and Clayton, 2005), and is inherited from the prescribed spacing of debris source nonuniformity.…”
Section: Discussionsupporting
confidence: 61%
“…The final stage of cliff reburial occurred during our study interval as the cliff exhausted the available topography, as suggested in Brun and others (2016). It is apparent, however, that the reworking of the debris surface by the cliff's backwasting led to thinner debris over a broad area (Bartlett and others, 2020). We note that the melt distance of the area occupied by the ice cliff in May was 3–3.6 m, whereas the peak melt distances (>4.5 m) occurred in an area not observed to be occupied by an ice cliff, and melt distances within the scallop area (>3 m) were twice the value of the surrounding area (1–1.9 m).…”
Section: Resultsmentioning
confidence: 99%
“…
Debris-covered glaciers are widespread in all mountain ranges around the globe (Herreid & Pellicciotti, 2020b;Scherler et al, 2018) and especially in High Mountain Asia (HMA), where half of the glaciers larger than 2 km 2 have more than 5% of their total area covered by a layer of rock debris (Herreid & Pellicciotti, 2020b) varying in thickness from centimeter to meter scale. These glaciers are often characterized by undulating, hummocky topography (Bartlett et al, 2020) and their surface is punctuated by supraglacial ponds, streams, and ice cliffs. Ice cliffs have been observed in all the main mountain ranges of the planet (
…”
mentioning
confidence: 99%